Cascaded photonic crystal fiber interferometers for refractive index sensing - Lim, Jun Long (2013)
We present a cascaded fiber device based on photonic crystal fiber (PCF) interferometers for refractive index (RI) sensing. The PCF modal interferometers have microbubbles at both sides of the splice regions. The microbubbles act as thick diverging lens that scatter light for efficient excitation of higher order cladding modes and attenuation of the core modes in the transmitted spectrum. Three resonance wavelengths are monitored, and their corresponding RI sensitivities are found to be 252, 187, and 207 nm/refractive index unit (RIU). The results, to our best knowledge, demonstrate that PCF interferometers with microbubbles are repeatable for high RI sensitivity, and the best crosstalk achievable is 0.295 nm/RIU.